EPID-27. GEOGRAPHIC BURDEN OF CNS TUMORS AND DENSITY OF NEURO-ONCOLOGISTS IN THE UNITED STATES. (12th November 2021) - Gregory, Timothy; Graber, Jerome
Abstract: CNS cancer care relies heavily on exam and imaging interpretation skills distinctive to a neurology-trained oncologist, and access to this subspecialty is increasingly more essential as targeted molecular therapies evolve. We sought to explore the supply of neuro-oncologists in terms of geographic CNS tumor incidence. Using the UCNS online directory, we generated a heat map representing the location (set to 75-mile radius) and density of active neuro-oncologists. We overlaid this data upon yearly incidence of CNS tumors per neuro-oncologist for each state using most recent CBTRUS data. We highlight the significant distance Americans outside of urban areas must travel for care and that isolation from academic centers and exclusion from clinical trials are substantial barriers to cancer care for a significant proportion of the population. Telemedicine may in part improve patient access to care and clinical trial participation, but significant state-to-state legal variability for providing telehealth services across state lines remains a national challenge. Short-term strategies for equitably meeting this subspecialty need may require policy changes that optimize employment of telemedicine, and long-term must ensure a robust fellowship pipeline with thoughtful incentivization and allocation of resources.